Harmful Effects of Pyraclostrobin on the Fat Body and Pericardial Cells of Foragers of Africanized Honey Bee - Inoue, Lais V. B. [UNESP]; Domingues, Caio E. C. [UNESP]; Gregorc, Aleš; Silva-Zacarin, Elaine C. M.; Malaspina, Osmar [UNESP] (MDPI, 2022)
Managed honey bees are daily exposed in agricultural settings or wild environments to multiple stressors. Currently, fungicide residues are increasingly present in bees’ pollen and nectar and can harm colonies’ production and survival. Therefore, our study aimed to evaluate the effects of the fungicide pyraclostrobin on the fat body and pericardial cells of Africanized honey bees. The foragers were divided into three experimental treatment groups and two controls: pyraclostrobin 0.125 ng/µL (FG1), 0.025 ng/µL (FG2), 0.005 ng/µL (FG3), untreated control (CTL), and acetone control (CAC). After five days of oral exposure (ad libitum), the bees were dissected and prepared for histopathological and morphometric analysis. The FG1-treated bees showed extensive cytoarchitecture changes in the fat body and pericardial cells, inducing cell death. Bees from the FG2 group showed disarranged oenocytes, peripheral vacuolization, and pyknotic nuclei of pericardial cells, but the cytoarchitecture was not compromised as observed in FG1. Additionally, immune system cells were observed through the fat body in the FG1 group. Bees exposed to FG3 demonstrated only oenocytes vacuolization. A significant decrease in the oenocyte’s surface area for bees exposed to all pyraclostrobin concentrations was observed compared to the CTL and CAC groups. The bees from the FG1 and FG2 treatment groups presented a reduced surface area of pericardial cells compared to the controls and the FG3 group. This study highlighted the harmful effects of fungicide pyraclostrobin concentrations at the individual bee cellular level, potentially harming the colony level on continuous exposure.
Keywords: Apis melliferaL; biomarkers; morphophysiology; residual concentrations; strobilurin fungicide